Estimating the effect of optimizing anticancer drug vials on medical costs in Japan based on the data from a cancer hospital - Koichi Matsuo; Hisanaga Nomura; Masanobu Uchiyama; Motoyasu Miyazaki; Osamu Imakyure (BMC, 2020)
Abstract Background The substantial increase in the use of expensive anticancer drugs has been accompanied by an increase in the amount of disposing residual liquid from drug preparations. Many Western countries, including the United States, have implemented drug vial optimization (DVO) to prevent the waste of anticancer drugs and have reported the reductions in the total drug costs. This study was designed to estimate the expected reduction in spending on anticancer drugs by Japanese cancer hospitals when DVO was implemented instead of individual preparations and to test the effectiveness of this approach. Methods We investigated the doses of drugs used and quantity specifications for individually prepared vials for patients who received anticancer drug treatment in December 2017 at the Outpatient Treatment Center of the National Cancer Center Hospital East. Based on these findings, we calculated the total quantity of each drug used on a given day, and the minimum cost for preparation of the number of specified combinations corresponding to the total cost (DVO preparation). Based on the differences in these two costs, we estimated the economic impact of implementing DVO. Results While the cost for anticancer drugs for the 1-month study period was US$3,305,595 (US$1 = \110) for individual preparations, the estimated cost for DVO preparations was US$3,092,955, equivalent to a reduction of US$212,640. Conclusions Based on these study results, implementation of DVO-based preparation of injectable anticancer drugs in Japan in 2017 would have resulted in saving approximately US$460 million. This calculation revealed the need for the Japanese government to modify the methods employed to calculate drug costs in the insurance system and develop policies for the proper and optimal use of medical resources.